Fragmentation analyses of rocks under high-velocity impacts using the combined finite-discrete element simulation - Yang, Tao; Ma, Hui; Weng, Lei; Liu, Yang; Chu, Zhaofei; Zhang, Penglin; Jin, Gang; Chang, Weixue (Frontiers in Earth Science, 2022)
The impact-induced fragmentation of rock blocks is regularly encountered during natural hazards (e.g., rockfalls, rockslides, and rock avalanches) in mountainous regions. To address the progressive damage and cracking characteristics of rocks due to high-velocity impact, the complex impact-induced fragmentation process was analyzed using the combined three-dimensional finite-discrete element method (3D-FDEM). The influences of the impact velocity on the dynamic fragmentation process, damage evolution, fragment characteristics, fragment flying velocity, and angle were systematically investigated. The parameters as input for simulation were first calibrated through the 3D uniaxial compression tests and rock-impact tests. Then, the complex fragmentation process of rock samples subjected to different impact velocities (i.e., 20-80 m/s) was simulated. The numerical results show that the number of cohesive elements following shear-dominated failures gradually increases with increasing the impact velocity. For the region closer to the impact face, a more substantial shear-dominated failure and a higher increase in Pshear/Ptensile can be observed. The fractal method can well describe the distribution of the equivalent fragment length, and the variations of the fractal dimension are consistent with that of the damage ratio, increasing linearly with impact velocity. Both the average and maximum flying velocities of the fragments increase linearly with increasing the impact velocity. However, the average flying angle of the fragments shows a sharp increase and then a slight increase with increasing the impact velocity.